Risk Perception Mental Health Impact and Coping Strategies during Covid 19 Pandemic among Health Care Workers - Fatima Chaudhry, Hassan Asghar, Chaudhry Umar Asghar, Amina Asghar, Heba Imtiaz (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the risk perception mental health impact and coping strategies during Covid-19 pandemic among health care workers. Study Design: Cross-sectional study. Place and Duration of Study: Department of Community Dentistry, Frontier Medical & Dental College, Abbottabad from 1st January 2021 to 31st December 2021. Methodology: Two hundred health care workers were given questionnaire for complete detailing their information regarding demographic, occupational, anxiety scoring and depression state. Results: The age of the health care workers was mostly within 26-40 years followed by greater than 18 years. It was observed that anxiety was presented at a mild score within doctors and other health care worker staff while it was seen to a moderate level within the nursing health care workers. Furthermore, the gender distribution of anxiety showed higher level of anxiety among females than males. Within genders a low risk perception was seen within males than females. Among the health care workers, the risk perception was highest in nurses followed by paramedic and other health care staff. Conclusion: Covid-19 has caused devastating effects on the psychological stability of the health care workers which needs to be properly assessed and addressed.